Probing the Role of Electrode Microstructure in the Lithium-Ion Battery Thermal Behavior. Issue 11 (1st January 2017) - Chen, Chien-Fan; Verma, Ankit; Mukherjee, Partha P.
Abstract : Safety and performance of lithium-ion batteries over a wide temperature window are of paramount importance, especially for electric vehicles. The safety concerns are predicated on the thermal behavior as the occurrence of local temperature excursions may lead to thermal runaway. In this work, the role of electrode microstructure and implications on the cell thermal behavior are examined. A microstructure-aware electrochemical-thermal coupled model has been proposed, which delineates the electrode-level thermal complexations due to the structure-transport-electrochemistry interactions. Detailed analysis of the spatio-temporal variation of the heat generation rates (ohmic, reaction and reversible contributions) for different electrode microstructural configurations is presented to explain the dominant factors causing temperature rise. The tradeoff between the cell performance and safety is discussed from an electrode-level, bottom-up view point. This study aims to provide valuable insights into potentially tuning electrode-level structural features as an internal safety switch toward limiting the Li-ion cell temperature rise during operation.